Fulminant Influenza B Myocarditis in a Pediatric Patient - McCormick, Amanda D.; Censoplano, Nina; Schumacher, Kurt R. (Journal of Pediatric Intensive Care, 2017)
Influenza B is a common viral illness in childhood. We report a 5-year-old previously healthy girl admitted with facial edema that developed severe acute myocarditis from influenza B infection. As her clinical course progressed, she ultimately developed severe, acute heart failure requiring extracorporeal membrane oxygenation for support.
Keywords: influenza; myocarditis; influenza B